IMPACT OF SWING ON THE FOOT ARCH - Marcel Sekereš; Linda Peťková; Daniel Gurín (Matej Bel University, 2021)
Swing is consider across his simpliness as complex exercise, which brings a lot of benefits. How swing effects the arch of foot is according to available resources little explored area. With weakened muscles, the arch decreases (flattening) even during the standing, resting phase. According to Hoke, no mechanism can replace the function m. posterior tibialis, m. tibialis anterior a m. flexor hallucis longus while maintaining the arch. The researchs shows that the occurrence of flat and high foot can be considered serious even in the younger population, which formed a sample in our research. Improper arching of the foot arch can also result in incorrect posture. That is why we decided in our research to focus on this possible effect of the kettlebell swing exercise. The main aim of our research was to find out the effect of the swing exercise on the arch of the foot and how a possible change in the footprint taken by the podoscope will show. On research has participated 16 respondents, most of them active sportsmen. Arch of foot was evaluated befor beginning of six weeks cycle of doing swing exercises three times per week and after at the end of the cycle by podoscope. The pictures captured by podoscope were evaluated by Chippaux-Smirak index, which characterized level of arch. After the anlysis of results has been shown statisticaly important effect of swing on arch of foot. In flat foot has been shown effect of increasing its arch and at high arch has been shown the oposite effect decreasing its arch. Partial aim was to find out the subjective feelings of the respondents after the end of testing, where lots of respondents experienced improvements in different eras. These findings by our research are opening the use of swing even as possible tool fot therapy or prevention of problems with foot arches.